Management tool to optimize energy and water consumption in the sanitary-ware industry. (1st October 2018) - Cuviella-Suárez, Carlos; Colmenar-Santos, Antonio; Borge-Diez, David; López-Rey, África
Abstract: Over the years the ceramic industry has been widely studied. However, little attention has been devoted to the particular area of sanitary-ware manufacturing, although it is a great consumer of energy and water. The aim of this research is to analyze and quantify how and where energy and water are consumed by mapping the whole process. Once the key points and amounts of consumption are located, a global map of single flows is established by thermodynamically modeling every relevant sub-process as a balance of mass and energy. The research focuses on demonstrating that this modeled map can be optimized by diverting energy flows from one sub-process to another searching for the minimum incoming energy within the global process, which derives in a minimization of residual energy, waste water and emissions. Results show that almost one third of the energy and emissions can be saved and more than a half of the water can be saved as well in the resin mold technology of manufacturing. This research provides a tool to know how the resources are consumed in the sanitary-ware industry and show the possibilities to reduce them as well as the global impact. Graphical abstract: Highlights: Energy, water and CO2 emissions reduction in a sanitary-ware factory. A model to optimize sanitary-ware factories design. Global assessment of reduction of energy, water and CO2 emissions in the sanitary-ware industrial sector. Economic improvements by remarkable reductions of resources.